Revisiting the bottleneck congestion model by considering environmental costs and a modal policy. Issue 3 (15th March 2016) - Bulteau, Julie
ABSTRACT: This article attempts to internalize the negative external effects (congestion and pollution) generated by using cars, by considering the urban tax tool. To do this, we provide the development of a microeconomic model of this urban toll system, in order to minimize the total social cost. Two modes of transportation are taken into account: cars and public transport, the latter being considered nonpolluting. The total social cost includes (a) the costs generated by the two modes of transport, (b) the congestion costs, and we add (c) environmental costs generated by using cars. Based on Arnott, De Palma, and Lindsey (1990, 1993), who developed a bottleneck congestion model, three alternative tolls are compared: a fine toll, a coarse toll, and a uniform toll. Thus, several types of urban toll are investigated and we also add a modal policy, which redistributes the gains from urban tax to public transport. We analyze the implementation of an economic tool and a modal policy to achieve a social optimum. Finally, we highlight that the uniform toll provides the greatest impact on car traffic reduction but induces the highest total social cost. A coarse toll and a uniform toll reduce the social cost in comparison with a no-toll equilibrium. We also point out that adding a modal policy to the toll is successful in reducing the total social cost. Numerical simulations back up this theoretical analysis.